Sub-decadal North Atlantic Oscillation variability in observations and the Kiel Climate Model - Reintges, Annika; Latif, Mojib; Park, Wonsun (Climate Dynamics, 2017)
The North Atlantic Oscillation (NAO) is the dominant mode of winter climate variability in the North Atlantic sector. The corresponding index varies on a wide range of timescales, from days and months to decades and beyond. Sub-decadal NAO variability has been well documented, but the underlying mechanism is still under discussion. Other indices of North Atlantic sector climate variability such as indices of sea surface and surface air temperature or Arctic sea ice extent also exhibit pronounced sub-decadal variability. Here, we use sea surface temperature and sea level pressure observations, and the Kiel Climate Model to investigate the dynamics of the sub-decadal NAO variability. The sub-decadal NAO variability is suggested to originate from dynamical large-scale air-sea interactions. The adjustment of the Atlantic Meridional Overturning Circulation to previous surface heat flux variability provides the memory of the coupled mode. The results stress the role of coupled feedbacks in generating sub-decadal North Atlantic sector climate variability, which is important to multiyear climate predictability in that region